Interpretasi Metode Dakwah dalam Al-Qur’an Surah an-Nahl Ayat 125 - Siti Hotiza; Faizah Binti Awad; Nurdin; Rahmawati; Fatira Wahidah (Gunung Djati Conference Series, 2022)
This study aims to discuss the da'wah method in the Qur'an surah an-Nahl verse 125. This study uses a qualitative approach through literature study by applying descriptive-analytical methods. The results and discussion in this study indicate that the da'wah method contained in the Qur'an surah an-Nahl verse 125 there are three methods namely al-hikmah, al-mau'izah al-hasanah, and wa Jadilhum bi al-lati hiya ahsan. . This study shows that the Qur'an surah an-Nahl verse 125 is one of the verses in the Qur'an that is often used as a reference for a preacher in applying the da'wah method that will always be in accordance with every condition of the times and circumstances of the da'i. 'i and mad'u.